The application of osmotically assisted reverse osmosis (OARO) processes for low-cost and sustainable zero-liquid discharge (ZLD) desalination - Peters, CD (2021)
Freshwater scarcity is a globally increasing threat that is aggravated by population growth, economic development, the concomitant increase in consumption, and global climate change. Potable water is mostly extracted from natural fresh water sources, such as rivers, lakes, and aquifers, as these facilitate the cheapest and least energy intensive means of extraction. However, unsustainable extraction rates, which exceed the natural refill rate, inevitably lead to their depletion. Global warming further amplifies freshwater scarcity in arid regions, as these regions face higher evaporation rates and a growing reduction in the annual rainfall.